مقاربة نظرية حول الإدارة الالكترونية - قوارح, أم الخير (جامعة الوادي - University of Eloued, 2018)
مما لاشك فيه أن الممارسة التنظيمية اخذت في التغير بفعل ارتباطها بالتطور التكنولوجي من جهة والتوجه العام للمنظمة من جهة اخرى. فانتقلت من صورة التنظيم الصناعي إلى صورة التنظيم المعرفي. وارتبط هذا الاخير بتنامي التوجه نحو مجتمع المعرفة. وعلى اثر ذلك كان لزاما احداث التجديد والاصلاح في التمكنات والميكانيزمات التنظيمية خاصة على مستواها الاداري، لتظهر الادارة الالكترونية كأحد هذه النواتج في ظل توفير فضاء تنظيمي يتسم السواء. عموما تقوم الادارة الالكترونية داخل المنظمة على التوظيف الامثل للتقنية الالكترونية في استغناء تدريجي عن الطرائق التقليدية في اداء العمل. جاء هذا المقال؛ كمحاولة لرفع الغموض حول مفهوم الادارة الالكترونية في مقاربة نظرية نعرض من خلالها مختلف ابعادها وخصائصها واهدافها.In fact, the organizational practice has known a lot of change, because of its relationship with the technological development on the one hand, and on the other with the general direction of the organization . It moved hence from the organization of the industry to an organization of knowledge. This latter is connected with the growing trend towards a knowledge community. Consequently , it is necessary to renew and reform the organizational mechanisms, especially at the administrative level, so that e-management deemed as one of these fruits. All in all ; the application of e-management in the organization is based on the optimal use of the electronic technology that gradually replaces the traditional working methods, in performing the organizational work. This article is a theoretical approach to e-management, through which we present its different dimensions, and its characteristics and objectives.
مقال
Keywords: الإدارة الالكترونية، تكنولوجيا المعلومات والاتصال، المنظمة.; e-Management; the organization; communication technologies.